Penerapan Teknologi Pakan Lengkap Ternak Itik dalam Program Pemberdayaan Wilayah Kecamatan Patampanua Kabupaten Pinrang - Syamsu, Jasmal Ahmari; Purwanti, Sri; Adzima, Ahmad Fauzan; Munir; Walinono, Andi Muh.Fuad Al Kautsar; Amal, Ichlasul (Yayasan Rahmatan Fidunya Wal Akhirah, 2025)
The application of complete feed technology to ducks is part of the Empowerment activities of Patampanua District, Pinrang Regency, in 2024. This activity increases productivity and efficiency in duck farming by demonstrating complete duck feed processing, at the Cenrana Farmers Group, Patampanua District, Pinrang Regency. The purpose of community service is to improve the skills of farmer group members in understanding and implementing complete feed technology, including feed raw materials, ration formulation techniques, duck feed nutritional quality, and complete duck feed processing techniques. The results of the implementation of community service show that the application of complete duck feed technology through a demonstration of feed processing based on local raw materials has been proven to increase the knowledge and skills of farmers. This can be seen from the increase in the average pre-test score (59.00 ± 6.05) to the post-test (70.76 ± 8.02), with significant differences in all aspects of the assessment. The active participation of farmers during the demonstration process, from grinding materials and mixing to storing feed, shows that the method of applying technology through practice-based accuracy, effective in improving technical skills and understanding in processing complete feed for ducks.